Identifikasi faktor Penerapan Green Supply Chain Management Pada Industri Furniture Kayu - Much Djunaidi; M. Abdul Azis Sholeh; Nur Muhammad Mufiid (Jurnal Teknik Industri, 2018)
Competition in the manufacturing industry continues to increase, along with the shift in consumer demands increasingly aware of environmental sustainability. Implementation of green supply chain management became one of the company's attention to answer the demands. The government has also regulated related regulations. In Indonesia, wood furniture industries related to environmental conservation have not applied Green Supply Chain Management (GSCM). This study examines the factors that encourage the implementation of GSCM in the wood furniture industry, by involving relevant stakeholders. The weight of the influencing factor is determined by the Analytical Hierarchy Process (AHP) method. The results show consumer behavior, support from top management, and organizational strategies that influence the application of GSCM predominantly.